Common Fixed Point Results for Compatible Map in Digital Metric Spaces - Dalal, Sumitra (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
The aim of this paper is to define the concept of compatible maps and its variants in the setting of digital metric spaces and establish some common fixed point results for these maps. Also, an application of the proposed results is quoted in this note.